2006
DOI: 10.1007/s10688-006-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Disjointness, divisibility, and quasi-simplicity of measure-preserving actions

Abstract: For weakly mixing flows, quasi-simplicity of order 2 implies quasi-simplicity of all orders. A uniformly divisible automorphism and a 2-quasi-simple automorphism are disjoint.Key words: weakly mixing flow, divisible ergodic system, quasi-simplicity, disjointness, pairwise independent joinings.The structure of self-joinings of a dynamical system gives information about the factors and the centralizer of its tensor products; it is also useful for the construction of counterexamples and for the study of Rokhlin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Hence we have the following In Theorem 5 below, we show that the SWR property for (T t α, f ) t∈R implies the FEJ-property. As an immediate consequence of this and of Theorem 3, Corollary 1.6 and the fact that mixing flows with the FEJ-property are multiple mixing [31] we get the following. …”
Section: Theorem 2 Letsupporting
confidence: 53%
See 1 more Smart Citation
“…Hence we have the following In Theorem 5 below, we show that the SWR property for (T t α, f ) t∈R implies the FEJ-property. As an immediate consequence of this and of Theorem 3, Corollary 1.6 and the fact that mixing flows with the FEJ-property are multiple mixing [31] we get the following. …”
Section: Theorem 2 Letsupporting
confidence: 53%
“…For m s 0 and N∪{0} l max( q m+1 8Cq m −1, 0) we will consider the following conditions on x, y ∈ T [compare with (31) and (32)]…”
Section: Proof Of Proposition 46 Part Bmentioning
confidence: 99%
“…Moreover, in [23], M. Ratner showed that the Ratner property survives under C 1 smooth time changes of horocycle flows, hence similar rigidity phenomena hold for time changes. One of the most important consequences of this property is that a mixing system with the Ratner property is mixing of all orders, see [21].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, one can show that if (T t ) t∈R has the SWR-property (and hence in particular if it has the SR-property), then it has a property the finite extension of joinings property (shortened as FEJ property), [10], which is a rigidity property that restricts the type of self-joinings that (T t ) t∈R can have [37,11]. We refer the reader to [13,37] for the definition of joinings and FEJ. Furthemore, it is well known that if (T t ) t∈R is mixing and has the FEJ property, then it is automatically mixing of all orders, [37].…”
Section: Ratner Properties Of Parabolic Divergencementioning
confidence: 99%